Evaluasi Implementasi P2L dalam Meningkatkan Ketahanan Pangan Keluarga pada KWT Kota Blitar - Palupi Puspitorini; Tri Endrawati; Alvita Sekar Sarjani; Ana Amiroh; Ramadhanty Cahyaning Rizky; Farra Dila Maharani (Universitas Islam Balitar, 2026)
This community service activity aimed to evaluate the implementation of the Sustainable Food Yard (Pekarangan Pangan Lestari/P2L) program by Women Farmer Groups in strengthening household food security in Blitar City. A quantitative approach was employed through a survey of 30 group members using structured questionnaires, observations, and documentation. Data were analyzed using descriptive statistics to assess participation, program effectiveness, and its impact on household food security. The results showed an 83.3% participation rate, with an average yard utilization of 25 m² per household. The program increased household food availability by 37.5% and expanded crop diversity from an average of three to seven plant species. Furthermore, 68.3% of households became self-sufficient in vegetable consumption, participants’ knowledge increased by 41.2%, household food expenditures decreased by IDR 150,000–300,000 per month, and program sustainability reached 76.7% after six months, despite limitations in facilities and technical assistance.